Faktor-Faktor yang Berkaitan dengan Kepuasan Rasa pada Makanan Katering Haji dan Implikasinya bagi Kesehatan - Suratman, Dadang; Mulyo, Gurid Pramintarto Eko (Poltekkes Kemenkes Bandung, 2026)
Background: Large-scale Hajj catering requires efficiency without compromising taste quality. The use of ready-to-use spice paste improves efficiency and consistency but may affect sensory quality. Taste satisfaction is also influenced by food handlers’ perception and experience. Objective: This study aimed to analyze factors associated with taste satisfaction in Hajj catering, including the use of ready-to-use spice paste, perceived importance of its use, and work experience of food handlers. Methods: A cross-sectional design with a quantitative approach supported by qualitative data was used. Data were collected through questionnaires from 31 catering staff selected by purposive sampling and semi-structured interviews. Analysis was performed using Fisher’s Exact test and Odds Ratio (OR) (α=0.05). Results: The use of ready-to-use spice paste and the perceived importance of its use were significantly associated with taste satisfaction (p<0.05). Perceived importance of spice paste use showed the strongest association with taste satisfaction (OR=9.90; 95% CI: 1.80–54.00). Work experience was not significantly associated with taste satisfaction (p>0.05). Most respondents reported moderate satisfaction with meal taste. Qualitative findings showed that chefs performed flavor fine-tuning to maintain sensory quality despite the use of ready-to-use spice paste. Conclusion: Taste satisfaction in Hajj catering meals is influenced by technical and perceptual factors related to spice paste use. Maintaining sensory quality through flavor adjustment remains important to support food acceptance. Further studies using direct health indicators are needed to confirm the health implications.